2021
DOI: 10.3390/f12060674
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Connectivity of Riparian Forests across a Gradient of Human Disturbance: The Potential of Copernicus “Riparian Zones” in Two Hydroregions

Abstract: The connectivity of riparian forests can be used as a proxy for the capacity of riparian zones to provide ecological functions, goods and services. In this study, we aim to test the potential of the freely available Copernicus “Riparian Zones” dataset to characterize the connectivity of riparian forests located in two European bioclimatic regions—the Mediterranean and the Central Baltic hydroregions—when subject to a gradient of human disturbance characterized by land-use/land-cover and hydromorphological pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The visual protocol results indicated that the riparian areas of both sub-watersheds are in good condition compared to many other studies in Greece and the Mediterranean [65][66][67]. This was expected since both sub-watersheds have limited anthropogenic impacts, especially agricultural activities.…”
Section: Discussionmentioning
confidence: 48%
“…The visual protocol results indicated that the riparian areas of both sub-watersheds are in good condition compared to many other studies in Greece and the Mediterranean [65][66][67]. This was expected since both sub-watersheds have limited anthropogenic impacts, especially agricultural activities.…”
Section: Discussionmentioning
confidence: 48%